Acetylation of histones and activity of antioxidant enzymes in cells of the callus culture of Arabidopsis thaliana - Jadko, S. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
Participation of histone deacetylase (HDA) in the regulation of the activity of antioxidant enzymes in callus culture of Arabidopsis thaliana under normal conditions is investigated. It is found that reducing the activity of HDA by inhibitor TCA increases the activities of ascorbate peroxidase (Apx), catalase (CAT), and thioredoxin (Trx). Possible mechanisms of the participation of HDA and histone acetyltransferase (HAT) in the epigenetic regulation of the activity of the investigated enzymes are discussed.